Maternal brachycephaly only does not influence umbilical artery resistance in late canine pregnancy - Sandes, Vitória Nayreli Freyre Gonçalves; Mendonça, Ligia Buzzá Roo de; Câmara, Diogo Ribeiro (Medicina Veterinária, 2021)
The popularity of canine brachycephalic breeds is rising in many countries of the world. Brachycephalic dogs are predisposed to developing brachycephalic obstructive airway syndrome (BOAS), resulting in lower partial pressure of oxygen in the arterial blood which might influence foetal haemodynamic parameters. Therefore, this study aimed to evaluate the influence of the maternal morphological characteristic (brachycephaly) on the resistive index of the umbilical artery (RIUA) during late pregnancy. This was a non-randomized and cross-sectional study that included data of foetuses from 42 clinically healthy pregnant bitches. The RIUA was measured in 137 foetuses, from 68 and 69 brachycephalic and non-brachycephalic bitches, respectively, between the seventh to ninth weeks of pregnancy. Gestational age was determined by ultrasonography according to foetal biparietal diameter (BP) by measuring two to four foetuses/pregnant bitch. Female dogs with at least one foetus diagnosed with a consistent heart rate below 180 bpm were not included in the present study. There was a significant weekly decrease in the RIUA of foetuses from both brachycephalic and non-brachycephalic bitches, from the seventh until the last week of evaluation. No differences were detected in the RIUA ate the same gestational week between foetuses from brachycephalic and non-brachycephalic bitches. In conclusion, maternal brachycephaly only is not able to induces RIUA changes in canine foetuses during late pregnancy.